Construction and immunogenicity of SARS-CoV-2 virus-like particle expressed by recombinant baculovirus BacMam - Hai Trong Nguyen; Darryl Falzarano; Volker Gerdts; Qiang Liu (Microbiology Spectrum, 2024)
ABSTRACT The pandemic severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) continues to evolve to give rise to variants of concern that can escape vaccine-induced immunity. As such, more effective vaccines are urgently needed. In this study, we evaluated virus-like particle (VLP) as a vaccine platform for SARS-CoV-2. The spike, envelope, and membrane proteins of the SARS-CoV-2 Wuhan strain were expressed by a single recombinant baculovirus BacMam and assembled into VLPs in cell culture. The morphology and size of the SARS-CoV-2 VLP as shown by transmission electron microscopy were similar to the authentic SARS-CoV-2 virus particle. In a mouse trial, two intramuscular immunizations of the VLP BacMam with no adjuvant elicited spike-specific binding antibodies in both sera and bronchoalveolar lavage fluids. Importantly, BacMam VLP-vaccinated mouse sera showed neutralization activity against SARS-CoV-2 spike pseudotyped lentivirus. Our results indicated that the SARS-CoV-2 VLP BacMam stimulated spike-specific immune responses with neutralization activity.IMPORTANCEAlthough existing vaccines have significantly mitigated the impact of the COVID-19 pandemic, none of the vaccines can induce sterilizing immunity. The spike protein is the main component of all approved vaccines for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) due primarily to its ability to induce neutralizing antibodies. The conformation of the spike protein in the vaccine formulation should be critical for the efficacy of a vaccine. By way of closely resembling the authentic virions, virus-like particles (VLPs) should render the spike protein in its natural conformation. To this end, we utilized the baculovirus vector, BacMam, to express virus-like particles consisting of the spike, membrane, and envelope proteins of SARS-CoV-2. We demonstrated the immunogenicity of our VLP vaccine with neutralizing activity. Our data warrant further evaluation of the virus-like particles as a vaccine candidate in protecting against virus challenges.